External Auditory Canal Cholesteatoma: Clinical and Radiological Features - Dongol,Kripa (2022)
Abstract Introduction External auditory canal cholesteatoma (EACC) is often misdiagnosed. Objectives To outline the clinical presentation of EACC, and to describe its radiological findings on high-resolution computed tomography (HRCT) of the temporal bone. Methods The clinical records of all patients diagnosed with EACC from April 2017 to March 2020 in a tertiary care center were retrospectively reviewed. The clinical presentation, the findings on the HRCT of the temporal bone, and the treatment provided were analyzed. Results A total of 9 patients, 7 males and 2 females, with a mean age of 30 years, were diagnosed with primary EACC. Six patients presented with otorrhoea, three, with otalgia, three. with hearing loss, and one with facial palsy. Some patients had multiple symptoms. The most common findings on otomicroscopy were destruction of the posterior and inferior canal walls, with cholesteatoma and intact tympanic membrane (six patients). Two patients had aural polyp, and one had a narrow ear canal due to sagging of the posterior canal wall. On HRCT, all nine patients showed soft-tissue density in the external auditory canal with erosion of the canal wall. The disease extended to the mastoid in eight cases, and to the cavity of the middle ear in one. There were three cases of dehiscence of the facial canal. Dehiscence of the dural and sinus plates was observed in two cases each. Eight patients underwent mastoidectomy, and one underwent debridement with canalplasty. Conclusion Review of the clinical and radiological findings is essential to reduce the rate of misdiagnosis.